Evaluation of the CIPP Model of the Religious Moderation Development Program at MTs YMI Wonopringgo Pekalongan - Abul Mafaakhir; Moh. Muslih; Titien Soewastiningsih Soebari (Saniya Institute, 2024)
This study aims to evaluate the effectiveness of religious facilitation program at MTs YMI Wonopringgo Pekalongan using CIPP (Context, Input, Process, Product) evaluation model. The research was conducted using descriptive qualitative method and case study approach. Data collection was done through in-depth interviews, observations and surveys. The research findings show that the program has been successful in achieving its goals, but some aspects still need improvement. Recommendations for program development include enriching learning materials, providing ongoing training for teachers, developing extracurricular activities, and increasing cooperation with the local community.